Effects of CYP3A4*22 and CYP3A5 on clinical outcome in patients treated with ticagrelor for ST-segment elevation myocardial infarction: POPular Genetics sub-study - Azzahhafi, Jaouad; Bergmeijer, Thomas O.; van den Broek, Wout W. A.; Chan Pin Yin, Dean R. P. P.; Rayhi, Senna; Peper, Joyce; Bor, Willem L.; Claassens, Daniel M. F.; van Schaik, Ron H. N.; ten Berg, Jurriën M. (Frontiers in Pharmacology, 2022)
Aims To determine the clinical efficacy, adverse events and side-effect dyspnea of CYP3A4*22 and CYP3A5 expressor status in ticagrelor treated patients. Methods and results Ticagrelor treated patients from the POPular Genetics randomized controlled trial were genotyped for CYP3A4*22 and CYP3A5*3 alleles. Patients were divided based on their genotype. In total 1,281 patients with ST-segment elevation myocardial infarction (STEMI) were included. CYP3A4*22 carriers (n = 152) versus CYP3A4*22 non-carrier status (n = 1,129) were not found to have a significant correlation with the primary thrombotic endpoint: cardiovascular death, myocardial infarction, definite stent thrombosis and stroke (1.3% vs 2.5%, adjusted hazard ratio 1.81 [0.43-7.62] p=0.42), or the primary bleeding endpoint: PLATO major and minor bleeding (13.2% vs 11.3%, adjusted hazard ratio 0.93 [0.58-1.50] p=0.77). Among the CYP3A4*1/*1 patients, CYP3A5 expressors (n = 196) versus non-expressors (n = 926) did not show a significant difference for the primary thrombotic (2.6% vs 2.5%, adjusted hazard ratio 1.03 [0.39-2.71] p=0.95), or the primary bleeding endpoint (12.8% vs 10.9%, adjusted hazard ratio 1.13 [0.73-1.76] p=0.58). With respect to dyspnea, no significant difference was observed between CYP3A4*22 carriers versus CYP3A4*22 non-carriers (44.0% vs 45.0%, odds ratio 1.04 [0.45-2.42] p=0.93), or in the CYP3A4*1/*1 group, CYP3A5 expressors versus CYP3A5 non-expressors (35.3% vs 47.8%, odds ratio 0.60 [0.27-1.30] p=0.20). Conclusions: In STEMI patients treated with ticagrelor, neither the CYP3A4*22 carriers, nor the CYP3A5 expressor status had a statistical significant effect on thrombotic and bleeding event rates nor on dyspnea.